Analysis of Robotic Building Skill for Electrical Engineering Student Based on Contextual Teaching & Learning with Structural Equation Modeling - Zuhrie, M. Syariffuddien; Basuki, Ismet; Buditjahjanto, I.G.P. Asto; Anifah, Lilik; Nurlaela, Luthfiyah (International Journal for Educational and Vocational Studies, 2019)
The objective of this research is to analyze the ability of electrical engineering students to build robots based on  Contextual Teaching and Learning (CTL) which is analyzed by Structural Equation Modeling (SEM) through IBM SPSS and IBM SPSS Amos software. CTL is able to aid teachers to explain teaching materials with real situations and also able to motivate students by connecting the knowledge with the real application. This research applied the development research design with the product in the form of the robotics lesson plan as a supporting or measuring tool to assess the ability to make a robot for electrical engineering students. The developed of the robotic module is the research results and monitoring results of the researchers from the year 2009 to 2015. Afterward, seven (7) validators validated the final module. The validators consist of instructional experts, educational experts, engineering experts, and grammarians. In addition, the average validator assessment result is 3.34, which fall into either category. Value probability level is above 0.5 (value = 0,522) then it is concluded there is improvement between constructs.